2007
DOI: 10.1227/01.neu.0000249271.56816.03
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Clot Volume Correlates With Age, Neurological Grade, and Blood Pressure

Abstract: SAH volume is correlated with clinical characteristics, including age, history of hypertension, admission systolic blood pressure, and WFNS grade. Anatomic aneurysm characteristics such as size and location do not reliably predict clot volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…However, those trials had some limitations in the following respects. First, between total ICH volume and SAH volume, they did not show which one was really associated with development of cerebral vasospasm 5)14). Second, some studies only included patients with Fisher grade 3 4)11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, those trials had some limitations in the following respects. First, between total ICH volume and SAH volume, they did not show which one was really associated with development of cerebral vasospasm 5)14). Second, some studies only included patients with Fisher grade 3 4)11).…”
Section: Discussionmentioning
confidence: 99%
“…Poor clinical grade (related to more severe hemorrhage), age and cigarette smoking have been reported as independent risk factors for symptomatic vasospasm 5)6)8)9)13)14)22)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age is well described as an independent predictor of outcome and advanced age has been consistently associated with lower incidence of angiographic vasospasm and DCI, 16,[30][31][32][33] aging is inversely related to favorable outcomes. 3 Older age is associated with larger subarachnoid clot volume, 34 and elderly patients (>60 years) have significant increased risk of poor outcome 3 because of higher rates of medical complications, 32,35 the main reason age was not included in our grading scale.…”
Section: 11mentioning
confidence: 99%
“…In intact cerebral autoregulation, arterial smooth muscle cells will react to intravascular pressure or changes in brain metabolism to maintain Rosen et al found that the volume of the subarachnoid clot is typically larger in elderly patients, which may be explained by brain atrophy with larger cistern spaces, and in hypertensive patients and patients presenting with higher WFNS grade (37). A larger subarachnoid clot may explain poor outcomes in these groups of patients.…”
Section: Discussionmentioning
confidence: 99%